FORMULASI KOMBINASI OPTIMUM FAKTOR-FAKTOR PRODUKSI DALAM PENGEMBANGAN USAHA PETERNAKAN SAPI PERAH RAKYAT DI KABUPATEN KLATEN - Erlyna Wida Riptanti (Caraka Tani: Journal of Sustainable Agriculture, 2008)
Klaten regency represent one of regency in Central Java province have big enough dairy cattle population. During six the last year shown that decreasing the amount of population and productivity. Related with dairy cattle productivity decreasing with the circumstance condition of daity cattle, feed and unfavourable livestock management from farmer. Farmer in management of livestock of dairy cattle hope to get highest earning. Small-big of the earning depended from amount product, price of product and production cost.The aims of the research are a) to know the level of optimum input use which can yield the maximum earnings, b) to know the change influence that happened at earnings in the event of change of coefficient of objective function. Basic method used in this reserach is descriptive. Determination of research area is purposive that is Klaten Regency with subdistrict Jatinom. And than taken two village are Bandungan and Kayumas. Farmer taken as sample in this research are farmer have adult dairy cattle. Every village taken are 20 respondent farmer of dairy cattle.The result of research shown that the maximum earnings can be reached in ranch of dairy cattle farmer of scale 5,62 UT of equal Rp 13.477.500 with the input use in the form of availibility of money for the capital of equal Rp 9.500.00, availibility of money for feed of equal to Rp 28.500.00 and availibility of money for medicine of equal to Rp 2.000.000. sensitivity analysis with change of coefficients objective function that are availibility of capital from 0,325-0,577, avalibility of money for feed from -0,121-0,362, avalibility of money for the IB from 0-0,388, avalibility of moneyfor medicine from 0,334-0,388, and availibility of water from 0-0,388 from optimal coefficient which still give the earnings for farmers.